Phylogenetic Estimation of Community Composition and Novel Eukaryotic Lineages in Base Mine Lake: An Oil Sands Tailings Reclamation Site in Northern Alberta. (10th September 2019) - Richardson, Elisabeth; Bass, David; Smirnova, Angela; Paoli, Lucas; Dunfield, Peter; Dacks, Joel B.
Abstract: Reclamation of anthropogenically impacted environments is a critical issue worldwide. In the oil sands extraction industry of Alberta, reclamation of mining‐impacted areas, especially areas affected by tailings waste, is an important aspect of the mining life cycle. A reclamation technique currently under study is water‐capping, where tailings are capped by water to create an end‐pit lake (EPL). Base Mine Lake (BML) is the first full‐scale end‐pit lake in the Alberta oil sands region. In this study, we sequenced eukaryotic 18S rRNA genes recovered from 92 samples of Base Mine Lake water in a comprehensive sampling programme covering the ice‐free period of 2015. The 565 operational taxonomic units (OTUs) generated revealed a dynamic and diverse community including abundant Microsporidia, Ciliata and Cercozoa, though 41% of OTUs were not classifiable below the phylum level by comparison to 18S rRNA databases. Phylogenetic analysis of five heterotrophic phyla (Cercozoa, Fungi, Ciliata, Amoebozoa and Excavata) revealed substantial novel diversity, with many clusters of OTUs that were more similar to each other than to any reference sequence. All of these groups are entirely or mostly heterotrophic, as a relatively small number of definitively photosynthetic clades were amplified from the BML samples.